Penggunaan Ringkasan Materi Essensial Sesuai SKL untuk Meningkatkan Nilai Try Out Biologi - Tri Vivery Perijanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
The purpose of this action to enhance the understanding of biology as a whole so as to improve the academic achievement that can be seen from the increase in value of test. Class actions performed included two cycles through the four stages, namely planning, action, observation and reflection. Through class actions carried out the verdict that the use of a summary of essential materials in accordance SKL can enhance students' understanding of biological materials because it can ease the burden on students in the study of biology as a whole class of biological materials in X to the biological material in class XII. However, keep in mind in making these summaries are designed for a structured arrangement with images made so attractive, clear, and if necessary choose the images that often come out in the previous state exams.